2008
DOI: 10.1086/587633
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Antifungal Medications in a Tertiary Care Center in Thailand: A Prospective Study

Abstract: The incidence and factors associated with inappropriate use of antifungal medications were studied in a Thai tertiary care center. The incidence of inappropriate antifungal use was 74% (in 42 of 57 patients). Isolation of Candida species from urine (P = .004) was a risk factor, whereas receipt of an infectious diseases consultation (P = .004) was protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 9 publications
1
19
0
2
Order By: Relevance
“…The use of antifungal drugs poses a daily challenge for professionals in many different specialties in modern hospitals . There are reportedly many inappropriate uses of triazole drugs in the United States, France, Spain and Thailand in terms of indications, drug dosages, duration of drug usage and other aspects which are due to guidelines not being followed.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The use of antifungal drugs poses a daily challenge for professionals in many different specialties in modern hospitals . There are reportedly many inappropriate uses of triazole drugs in the United States, France, Spain and Thailand in terms of indications, drug dosages, duration of drug usage and other aspects which are due to guidelines not being followed.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In a study of antifungal use at a tertiary care centre in Thailand, inappropriate use was identified in 70% (42/57) of cases . Multivariate analysis found that isolation of Candida species from urine was associated with inappropriate antifungal use, whereas receipt of an infectious disease consultation was protective against inappropriate use.…”
Section: Appropriateness Rates For Antifungal Drugs Are Lowmentioning
confidence: 99%
“…For quality assessment of IFI prophylaxis and treatment in routine care, evidence‐based guidelines have been used as the benchmark criteria. Analyses in different countries using guidelines for quality assessment of antifungal treatment have shown areas for improvement by classifying 40%‐43% of antifungal prescriptions as inappropriate . Data on the quality of IFI prophylaxis and therapy in German hospitals are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses in different countries using guidelines for quality assessment of antifungal treatment have shown areas for improvement by classifying 40%-43% of antifungal prescriptions as inappropriate. [18][19][20][21] Data on the quality of IFI prophylaxis and therapy in German hospitals are limited. As frequently discussed, randomised controlled trials refer to a precisely defined design and a homogenous and selected patient population, while in clinical practice, patients are much more heterogeneous.…”
mentioning
confidence: 99%